2007
DOI: 10.1590/s0034-72992007000600011
|View full text |Cite
|
Sign up to set email alerts
|

Verificação das respostas do mismatch negativity (MMN) em sujeitos adultos normais

Abstract: Mi smatch Negativity (MMN) is used to evaluate the central auditory system. Aim: to characterize the MMN, in normal subjects. Materials and methods: prospective study, 12 subjects, six males and six females, between the ages of 18 and 24. "Mann-Whytnei" test. Exams: Pure Tone Audiometry (PTA), Tympanometry, Otoacoustic Emissions and Short and Long Latency Auditory Potentials (MMN). Results: in MMN variable amplitude, the mean value was of -2.757 µV and -3.548 µV, CZA1 and CZA2; of 1.435 µV and -1.867 µV, CZA1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 19 publications
2
22
1
5
Order By: Relevance
“…The scientific literature emphasized the importance of verifying the use of MMN in the infant population and the need to know its applications in clinical practice (12) . Authors reported that MMN can be used to objectively evaluate patients with difficulty or impairment in communication, auditory discrimination, difficulty to respond consistently to stimulation, and in noncollaborative individuals, in order to evaluate the discrimination of different acoustic stimuli (1,41) . This review confirms that described in the literature, when it certifies that MMN applications are broad and include children with reading and writing difficulties, AD, dyslexia, stuttering, autism spectrum disorder, ADHD, auditory processing disorder, repetitive otitis …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The scientific literature emphasized the importance of verifying the use of MMN in the infant population and the need to know its applications in clinical practice (12) . Authors reported that MMN can be used to objectively evaluate patients with difficulty or impairment in communication, auditory discrimination, difficulty to respond consistently to stimulation, and in noncollaborative individuals, in order to evaluate the discrimination of different acoustic stimuli (1,41) . This review confirms that described in the literature, when it certifies that MMN applications are broad and include children with reading and writing difficulties, AD, dyslexia, stuttering, autism spectrum disorder, ADHD, auditory processing disorder, repetitive otitis …”
Section: Discussionmentioning
confidence: 99%
“…Changes in any portion of the auditory pathway prevent the development of these abilities from occurring fully (1) . Therefore, it is recommended that, in order to obtain an audiological diagnosis with more accuracy, objective and subjective assessment methods should be associated (2) .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations